Racism by another name : black students, overrepresentation, and the carceral state of special education - Hines, Dorothy E.; Boveda, Mildred; Lindo, Endia J. (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Racism by Another Name: Black Students, Overrepresentation, and the Carceral State of Special Education is a thought-provoking and timely book that provides a landscape for understanding and changing educational (in)opportunities for Black Students who are identified for special education. This book provides a historical and contemporary analysis through the eyes of Black children and their families how they navigate and push against inequitable schooling, how they are reframing discourse about race, dis/ability, and gender in schools, how educators, administrators, and school counselors contribute to disproportionality in special education, and ways that parents are collectively organizing to dismantle injustices and the carceral state of special education. Each chapter provides a ground level view of what Black students with dis/abilities experience in the classroom, and examines how the intersection of race, dis/abilty, and gender subject Black students to dehumanizing experiences in school. The book uses qualitative and quantitative approaches to exploring the material realities of Black students who are isolated in separate and mainstream classrooms. Drawing from Critical Race Theory, DisCrit, Critical Race Feminism, and other race-centered frameworks this book challenges hegemonic norms of schools that reinforce inequality and racial segregation in special education. At the end of each chapter the authors present practitioner-based notes and resources for readers to expand their knowledge of how Black students, their family, and guardians advocate for themselves and their own children. This book will leave educational advocates for Black children with a clearer understanding of the obstacles and successes that they encounter when striving for a just and equitable education. Additionally, the book challenges readers to be active agents of change in their own schools and communities"-- Provided by publisher.
Keywords: African Americans with disabilities -- Education.; African American children -- Education.; Learning disabled children -- Education.; Special education -- Social aspects -- United States.; Educational equalization -- United States.; Education -- Inclusive Education.; Educational strategies and policy: inclusion.; elektronické knihy; electronic books